Educational Employees' Perceptions Regarding Changes in Educational Organizations - Ozdemir, Tuncay Yavuz; Karakose, Turgut; Uygun, Harun; Yirci, Ramazan (Expert Projects Publishing, 2016)
The purpose of this study is to determine the perceptions of educational employees regarding change with regards to various variables. The study was carried out with a qualitative design. An interview form compatible with the study aims was created and content and face validity of the form was determined by consulting with expert opinion. Research findings suggest that change is required in schools and that changes should begin with upper management. In addition, because of a lack of information in educational organizations and because employees were not motivated by their managers regarding change, a resistance against change was detected. When viewed from this perspective, in order to cope with this resistance and promote change successfully, employees are required to agree with the decision by way of making an effective plan.
Keywords: educational organizations; change; resistance against change; educational employees